24h Quantitative-EEG and in-vivo glutamate biosensor detects activity and circadian rhythm dependent biomarkers of pathogenesis in Mecp2 null mice - Michael V Johnston; Simon eAmmanuel; Cliona eODriscoll; Amy eWozniak; Sakkubai eNaidu; Shilpa Dattatray Kadam (Frontiers in Systems Neuroscience, 2014)
Mutations in the X-linked gene encoding methyl-CpG-binding protein 2 (Mecp2) cause most cases of Rett syndrome (RTT). Currently there is no cure for RTT. Abnormal EEGs are found in 100% of RTT cases and are associated with severe sleep dysfunction, the cause of which is not well understood. Mice deficient in MeCP2 protein have been studied and characterized for their neuropathological and behavioral deficits to better understand RTT. With the goal to study the non-ictal EEG correlates in symptomatic Mecp2 KO mice (Mecp2tm1.1Bird/y), and determine novel EEG biomarkers of their reported progressive neurodegeneration, we used 24h video-EEG/EMG with synchronous in-vivo cortical glutamate biosensor in the frontal cortex. We scored the EEG for activity states and spectral analysis was performed to evaluate correlations to the synchronous extracellular glutamate fluctuations underlying Mecp2 inactivation as compared to WT. Significant alterations in sleep structure due to dark cycle specific long wake states and poor quality of slow-wave sleep were associated with a significant increase in glutamate loads per activity cycle. The dynamics of the activity-state-dependent physiological rise and fall of glutamate indicative of glutamate homeostasis was significantly altered in the KO mice. Colorimetric quantitation of absolute glutamate levels in frontal cortex also indicated the presence of significantly higher levels in KO. This study for the first time found evidence of uncompensated sleep deprivation-like EEG biomarkers that were associated with glutamate homeostatic dysfunction in the Mecp2 KO mice.